Patient Satisfaction in Medicine and Dentistry - Kelvin I. Afrashtehfar; Mansour K. A. Assery; S. Ross Bryant (International Journal of Dentistry)
Health professionals, such as medical and dental clinicians, have scant understanding of patients’ experiences and perceptions of satisfaction. Nevertheless, implementing a patient-reported outcome measures (PROMs) research practice in surgical sciences is necessary. Hence, the objective of this article was to better understand patients’ satisfaction with their medical and dental care. The methods of the current article are based on a narrative review of the literature strategy. A literature review was conducted using both EMBASE and Medline databases up to July 12, 2020, by combining keywords and terms related to “satisfaction theories” and “patient satisfaction,” and “medicine” or “dentistry/stomatology/odontology.” Patient satisfaction’s multidimensional nature has been established since the perceived reasons for satisfaction varied widely among patients. Many aspects of treatment influence participant satisfaction at different stages of the intervention process. An improved understanding of the basis for managing patients’ expectations with information reiteratively and efficiently may ultimately reduce patients’ potential for negative feelings toward the medical and dental treatment experience. Lastly, the consumerist method may misrepresent the still undertheorized concept of satisfaction in health service.